Adult Attachment, Emotion Dysregulation, and Symptoms of Depression and Generalized Anxiety Disorder. (18th January 2013) - Marganska, Anna; Gallagher, Michelle; Miranda, Regina
<x xml:space="preserve">Abstract</x> Differences in attachment style have been linked to both emotion regulation and psychological functioning, but the emotion regulatory mechanism through which attachment style might impact symptoms of depression and anxiety is unclear. The present study examined the explanatory role of emotion dysregulation in the relation between adult attachment style and symptoms of depression and generalized anxiety disorder (GAD) in a sample of 284 adults. Secure attachment was associated with lower depression and GAD symptoms and lower emotion dysregulation, whereas insecure attachment styles were generally associated with higher depression and GAD scores and higher emotion dysregulation. Perceived inability to generate effective emotion regulation strategies mediated the relation between insecure attachment and both depression and GAD symptoms. Nonacceptance of negative emotions and inability to control impulsive behaviors emerged as additional mediators of the relation between insecure attachment styles and GAD symptoms. The differential contribution of attachment style and emotion regulation to the prediction of depression and GAD symptoms may reflect differences in vulnerability to depression and GAD.